Management of Zakat, Infaq and Sadaqah Funds in Improving the Quality of Life of Mustahik - Hanin Nur Alinda; Nasrulloh Nasrulloh (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2023)
one of the goals of national development is to create a just and prosperous society, both materially and spiritually. To support national development goals, the government can collaborate with LAZ/BAZNAS to alleviate poverty with good ZIS (Zakat, Infaq and Sadaqah) fund management, which is expected to be able to improve Mustahiq's quality of life. This research aims to determine the Management of ZIS Funds (Zakat, Infaq and Sadaqah) at LAZISMU Jombang in improving Mustahiq's quality of life. The results of the study show that the management of ZIS funds (Zakat, Infaq and Sadaqah) must refer to PSAK Regulation No. 109 concerning financial accounting, which regulates the recognition, measurement, presentation and disclosure of zakat, infaq and sadaqah transactions. In empowering ZIS Funds (Zakat, Infaq and Sadaqah) by the Law No. 23 of 2011 in the distribution of zakat management to support the ZIS (Zakat, Infaq and Sadaqah) funds received are intended for the eight asnaf (fakir, poor, amil, convert, riqab (enslaved person), gharimin, fisabilillah, ibn sabil) group to improve the quality of life of mustahiq through programs namely (1) grebek: prayer for orphans (2 ) achieving the blessings of fajr alms (3) caring for honorary teachers (4) mentari scholarship (5) disaster alert (6) healthy assistance alms (7) mustahiq rises empowered.